2015
DOI: 10.1111/ggi.12571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health Baduanjin Qigong for mild to moderate Parkinson's disease

Abstract: BQG improved the gait performance, functional mobility and sleep quality in older adults with PD at the 6-month follow up. It is as an alternative home exercise program for older adults in rehabilitation for PD. Geriatr Gerontol Int 2016; 16: 911-919.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
122
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 23 publications
4
122
0
2
Order By: Relevance
“…Sample size in the eligible studies ranged from 20 to 222. When compared to Baduanjin Qigong intervention groups, study participants in the control groups were asked to keep either their original lifestyle [9, 13, 17, 18, 20, 32–35], educational lessons relating to diseases [14, 15, 36, 37], regular drug treatment [38, 39], regular healthcare [2, 40], or daily self-walking [11, 41]. Study participants in the Baduanjin Qigong intervention groups (intervention period ranging from 4 to 24 weeks) experienced Baduanjin Qigong exercise duration ranging from 30 to 90 minutes, along with the frequency of weekly sessions from 2 to 7.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample size in the eligible studies ranged from 20 to 222. When compared to Baduanjin Qigong intervention groups, study participants in the control groups were asked to keep either their original lifestyle [9, 13, 17, 18, 20, 32–35], educational lessons relating to diseases [14, 15, 36, 37], regular drug treatment [38, 39], regular healthcare [2, 40], or daily self-walking [11, 41]. Study participants in the Baduanjin Qigong intervention groups (intervention period ranging from 4 to 24 weeks) experienced Baduanjin Qigong exercise duration ranging from 30 to 90 minutes, along with the frequency of weekly sessions from 2 to 7.…”
Section: Resultsmentioning
confidence: 99%
“…Concealed allocation, blinding of participants, and blinding of therapists were not observed in all RCTs, which is acceptable because of nonpharmacological clinical trials [4244]. Blinding of assessors was present in 12 RCTs [9, 11, 1315, 20, 32, 35–37, 40, 41] but not employed in 7 RCTs [2, 17, 18, 33, 34, 38, 39]. Of 19 RCTs, only four RCTs were observed that the dropout rate was greater than 15% [2, 20, 32, 36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations